The effectiveness of complex treatment of generalized periodontitis in patients with a predominance of sympathetic nervous system with using Tantum Verde® in the long-term follow-up - Батіг, Віктор Маркіянович; Леснухіна, Ганна Леонтьєвна (Actual Dentistry, 2019)
Objectives. In the pathogenesis of generalized periodontitis significant place belongs to various systemic diseases. In recent years, growing interest in studying the peculiarities of the autonomic nervous system to the development of generalized periodontitis. Marked certain peculiarities of the various pathological conditions depending on the patient's autonomic nervous system that must be considered during their treatment. Given this proposed medicsment composition for treatment of patients with generalized periodontitis with prevalence of sympathetic autonomic nervous system. Aim. The determination of the clinical efficacy of the proposed integrated treatment of generalized periodontitis in patients with predominance of the sympathetic nervous system in the long-term follow-up. Materials and methods. Clinical investigation was conducted on groups of 25 patients with generalized periodontitis and prevalence of the sympathetic nervous system. Medicamental treatment was performed using proposed sedation composition and mouthrinsing of Tantum Verde® solution. Patients were conducted a comprehensive examination of periodontal tissue before treatment and after treatment. To evaluate the clinical efficacy of treatment used Schiller-Pisarev test (1962), the index of PMA by C. Parma (1961), hygienic index ОНІ-S Green-Vermillion (1964), the vacuum test by Kulazhenko (1961). Results. As a result of the investigation it was found that the usage of the proposed sedation composition in thecomplex therapy of patients with generalized periodontitis can effectively inhibit the dystrophic-inflammatory process in periodontal tissues in the long-term follow-up. The use of antiinflammatory drug Tantum Verde® increases the effectiveness of treatment. This confirms by the decline in the index PMA, increase the time of formation of hematoma during the vacuum tests on Kulazhenko, improving oral hygiene. Conclusions. Usage of the proposed sedation composition with mouthrinsing of Tantum Verde® solution increases the effectiveness of treatment of generalized eriodontitis in patients with predominance of the sympathetic nervous system in the long-term follow-up. Key words: generalized periodontitis, patients with predominance of the sympathetic nervous system, Tantum Verde®.